Development and validation of mobile based decision support system for Human Physical Drudgery Index (HPDI) - KUNDU, TAMAL; KUMAR, MUKESH; JOSHI, PRATIBHA; BHARADWAJ, ANSHU; MARWAHA, SUDEEP; PAL, SOUMEN (The Indian Journal of Agricultural Sciences, 2021)
The use of mobile applications and decision support system for agriculture is important in today's era. To enrich agriculture various mobile applications have been developed by different research institutes in NARES which are helping the farmers in their cultivation practices. In the present study, a mobile application named "HPDI Ergon" has been developed with intent to mapping of drudgery in physiological and psychological components and biomechanical evaluation of agricultural activities. In this respect the app named "HPDI Ergon" was developed during 2019-20 in computer application at ICAR-ISARI, New Delhi to assesses the drudgery involved in the work and give recommendation to mitigate it. In this app farmers are assessed based on different physiological and postural ergonomics parameters which includes heart rate, energy expenditure rate, total cardiac cost of work, physiological cost of work, human physical drudgery index variable etc. and conclusion is drawn on physiological and drudgery limitations. The app is developed using Android Studio and Java programming language. Individual registered farmers are selected to undergo different ergonomics and drudgery analysis. The data generated by different analysis is stored in the database which is implemented using SQLite database. Based on the results of all the ergonomic analysis and drudgery analysis using HPDI conclusion is drawn regarding whether there is any need of changing or improving the working condition or not. Accordingly, different suggestions and various improved tools are provided to the farmers for reducing their both physiological stress and drudgery in their working environment.